(untitled) (Biological Sciences - PJSIR, 1999)
A few mixed ligand macrocycJic complexes of Cr (III) and Co (III) of the formula trans [M(X2) L] CI2 where M =Cr (III), Co (III); X = anion of acetic acid (Ac), propionic acid (Pr), butyric acid (Bu): L= 5, 7, 7,12,14, 14-hexamethyl-l, 4,8, II, -tetraazacyclotetradeca-t, II-diene dihydro dibromide dihydrate (L. 2HBr. 2HP) have been synthesized and characterized, by elemental analyses, conductometric, magnetic measurements, IR and electronic spectral studies, The complexes are low- spin species with a trans configuration.